Peran Guru Pendidikan Agama Hindu Dalam Menanamkan Filosofi Pendidikan Multikultural Bagi Siswa Hindu Di SMPN 2 Basarang Kabupaten Kapuas - I Gede Dharman Gunawan; Kadek Sukiada; I Ketut Subagiasta; I Gede Arya Juni Arta (Jurnal Penelitian Agama Hindu, 2022)
This study aims to analyze the role of Hindu religious education teachers in instilling a philosophy of multicultural education for Hindu students at SMPN 2 Basarang, Kapuas Regency. Indonesia is a multicultural country consisting of different tribes, languages and religions. This diversity on the one hand is an advantage and wealth of the nation that must be maintained. But on the other hand, this diversity can be a potential for conflict in society. Therefore, an understanding of the nation's motto "Unity in Diversity" must be instilled in the younger generation from an early age so that they are able to play a role in maintaining unity amidst a pluralistic nation. one of the efforts that can be realized in response to this problem is to implement the concept of multicultural education in education in Indonesia. With the role of Hindu religious education teachers in instilling a philosophy of multicultural education for Hindu students, it is hoped that they can improve the quality of education and learning for Hindu students at SMPN 2 Basarang. As for educational institutions, it can later be used as a reference in providing education and learning based on multicultural education at SMPN 2 Basarang, Kapuas Regency.